2007
DOI: 10.1111/j.1471-4159.2007.04778.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐synuclein protects cerebellar granule neurons against 6‐hydroxydopamine‐induced death

Abstract: The physiological role of alpha-synuclein, a protein found enriched in intraneuronal deposits characterizing Parkinson's disease, is debated. While its aggregation is usually considered linked to neuropathology, its normal function may be related to fundamental processes of synaptic transmission and plasticity. By using antisense oligonucleotide strategy, we report in this study that alpha-synuclein silencing in cultured cerebellar granule cells results in widespread death of these neurons, thus demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 83 publications
7
40
1
1
Order By: Relevance
“…As previously demonstrated [22,30], exposure of differentiated rat CGNs to the dopaminergic toxin 6-OHDA (20 µ M ) resulted in approximately 50% cell death after -24 h (fig. 1a).…”
Section: Resultssupporting
confidence: 50%
“…As previously demonstrated [22,30], exposure of differentiated rat CGNs to the dopaminergic toxin 6-OHDA (20 µ M ) resulted in approximately 50% cell death after -24 h (fig. 1a).…”
Section: Resultssupporting
confidence: 50%
“…A recent communication (58) states, based on antisense oligonucleotide Syn silencing, that the protein has an essential pro-survival role toward primary neurons. Previous work has demonstrated that wild-type but not mutated Syn delayed death of neuronal cells after serum withdrawal (59), and protected cells by preventing activation of cell death-inducing proteins (caspases, p53, and Bad) (57,60).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated here the potent impact of peptide delivery on PMO SSO therapy. In addition to SMA, other diseases for antisense oligonucleotide therapies include ALS (56, 57), Huntington's disease (58,59), and Parkinson's disease (60,61), which all ideally require both systemic and CNS SSO delivery. Future work will focus on extending further the clinical applications of Pip-PMOs.…”
Section: Discussionmentioning
confidence: 99%